Direct Organogenesis of Passiflora foetida L. through Nodal Explants (Plant Tissue Culture and Biotechnology, 2012)
DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11266Plant Tissue Cult. & Biotech. 22(1): 87-91, 2012  (June)